Evaluation of Renewable Energy System For Sustainable Development - Faraji Abdolmaleki Shoeib (EDP Sciences, 2021)
This study reviews sustainable development (SD) elements through a holistic literature review to consider the relationship between SD indicators in the renewable energy (RE) sector, to identify critical drivers and methodologies needed to solve sustainability problems in RE. Through a systematic review, some compatible articles are selected from the electronic libraries. Driven information is employed to make a database that gives themes, dimensions, and indicators. Afterward, the sustainability evaluation of RE systems is investigated as an objective. Scopes and themes regarding SD and RE are investigated. As a result, SD indicators, RE systems, energy and sustainability, environmental sustainability assessment, energy security, electricity/power production, and energy geopolitics are the most existing scopes. Eleven sustainability frameworks, which scholars have used to consider RE sustainability, are identified appropriately. As a result, key dimensions are environmental, economic, social, technical, and institutional drivers. Therefore, indicators and criteria are reviewed for the top five drivers. Some of the most important of these indicators are: social (acceptability, job creation, social benefit, impact on health), economic (investment cost, operation, maintenance cost, and energy cost), environmental (CO2 emission, land use, impact on ecosystem, NOx and SOx emissions, GHG emission reduction, particle emission, noise), technical (efficiency, reliability, resource availability, maturity, safety, primary energy ratio, feasibility), and institutional (legal regulation of activity, government support, political stability, absence of violence/terrorism). Also, methodologies are examined to solve the challenge of sustainability evaluation. Literature review, MCDM techniques, LCA, PCA, and statistical methods are among the most widely used. Therefore, fully understanding the evaluation elements of SD in RE systems and having a database can speed up such studies.